2015
DOI: 10.3390/ma8115407
|View full text |Cite
|
Sign up to set email alerts
|

Surface Irregularity Factor as a Parameter to Evaluate the Fatigue Damage State of CFRP

Abstract: This work presents an optical non-contact technique to evaluate the fatigue damage state of CFRP structures measuring the irregularity factor of the surface. This factor includes information about surface topology and can be measured easily on field, by techniques such as optical perfilometers. The surface irregularity factor has been correlated with stiffness degradation, which is a well-accepted parameter for the evaluation of the fatigue damage state of composite materials. Constant amplitude fatigue loads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Yang et al 23,24 provided two methods to predict the statistical distribution of residual stiffness according to the presence or absence of historical data in the laboratory. Zuluaga-Ramı´rez et al 25,26 applied constant-amplitude fatigue loads and realistic variableamplitude loads which represent real in-flight conditions to ''dog bone'' shaped tensile specimens, and found that the coupons cycled with higher severity loads present faster stiffness degradation, which confirms that the stiffness degradation can be employed to determine the damage state due to fatigue loads.…”
Section: Introductionmentioning
confidence: 98%
“…Yang et al 23,24 provided two methods to predict the statistical distribution of residual stiffness according to the presence or absence of historical data in the laboratory. Zuluaga-Ramı´rez et al 25,26 applied constant-amplitude fatigue loads and realistic variableamplitude loads which represent real in-flight conditions to ''dog bone'' shaped tensile specimens, and found that the coupons cycled with higher severity loads present faster stiffness degradation, which confirms that the stiffness degradation can be employed to determine the damage state due to fatigue loads.…”
Section: Introductionmentioning
confidence: 98%
“…The area of tear was compared with 3 D ×1.8 as a reference, and the tear evaluation factor could be obtained. Zuluaga-Ramírez et al 16 correlated the surface irregularity factor with stiffness degradation, and proposed a new method for evaluating the damage state of CFRP. The surface irregularity factor of CFRP was measured by optical method, and the fatigue damage of material was evaluated by equal-amplitude fatigue load and real variable-amplitude load.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber reinforced polymer (CFRP) laminates are increasingly utilized in the aerospace and civil engineering fields for their low weight, high strength, and high stiffness [ 1 , 2 , 3 ]. During the long-term operation of CFRP laminated beam components, such as aircraft wings and wind turbine blades, cracks can occur on their surfaces, jeopardizing the integrity and safety of the whole structures [ 4 , 5 , 6 ]. Thus, identifying cracks in CFRP laminated beam is of great significance [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%